Anastrozole versus tamoxifen in postmenopausal women with ductal carcinoma in situ undergoing lumpectomy plus radiotherapy (NSABP B-35): a randomised, double-blind, phase 3 clinical trial. Issue 10021 (27th February 2016) - Margolese, Richard G; Cecchini, Reena S; Julian, Thomas B; Ganz, Patricia A; Costantino, Joseph P; Vallow, Laura A; Albain, Kathy S; Whitworth, Patrick W; Cianfrocca, Mary E; Brufsky, Adam M; Gross, Howard M; Soori, Gamini S; et al.
Summary: Background: Ductal carcinoma in situ is currently managed with excision, radiotherapy, and adjuvant hormone therapy, usually tamoxifen. We postulated that an aromatase inhibitor would be safer and more effective. We therefore undertook this trial to compare anastrozole versus tamoxifen in postmenopausal women with ductal carcinoma in situ undergoing lumpectomy plus radiotherapy. Methods: The double-blind, randomised, phase 3 National Surgical Adjuvant Breast and Bowel Project (NSABP) B-35 trial was done in 333 participating NSABP centres in the USA and Canada. Postmenopausal women with hormone-positive ductal carcinoma in situ treated by lumpectomy with clear resection margins and whole-breast irradiation were enrolled and randomly assigned (1:1) to receive either oral tamoxifen 20 mg per day (with matching placebo in place of anastrozole) or oral anastrozole 1 mg per day (with matching placebo in place of tamoxifen) for 5 years. Randomisation was stratified by age (<60 vs ≥60 years) and patients and investigators were masked to treatment allocation. The primary outcome was breast cancer-free interval, defined as time from randomisation to any breast cancer event (local, regional, or distant recurrence, or contralateral breast cancer, invasive disease, or ductal carcinoma in situ), analysed by intention to treat. This study is registered withClinicalTrials.gov, numberNCT00053898, and is complete. Findings: Between Jan 1, 2003, and June 15, 2006, 3104 eligible patients were enrolled and randomly assigned to the two treatment groups (1552 to tamoxifen and 1552 to anastrozole). As of Feb 28, 2015, follow-up information was available for 3083 patients for overall survival and 3077 for all other disease-free endpoints, with median follow-up of 9·0 years (IQR 8·2–10·0). In total, 212 breast cancer-free interval events occurred: 122 in the tamoxifen group and 90 in the anastrozole group (HR 0·73 [95% CI 0·56–0·96], p=0·0234). A significant time-by-treatment interaction (p=0·0410) became evident later in the study. There was also a significant interaction between treatment and age group (p=0·0379), showing that anastrozole is superior only in women younger than 60 years of age. Adverse events did not differ between the groups, except for thrombosis or embolism—a known side-effect of tamoxifen—for which there were 17 grade 4 or worse events in the tamoxifen group versus four in the anastrozole group. Interpretation: Compared with tamoxifen, anastrozole treatment provided a significant improvement in breast cancer-free interval, mainly in women younger than 60 years of age. This finding means that women will benefit from having a choice of effective agents for ductal carcinoma in situ. Funding: US National Cancer Institute and AstraZeneca Pharmaceuticals LP.